Physicochemical and Organoleptic Characteristics of Purple Corn (Zea mays L.) Extract Ice Cream: The Effect of Skim Milk and CMC Addition - Rahmati, Firdaus; Rosida, Rosida; Munarko, Hadi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Ice cream is a popular frozen dessert widely consumed due to its creamy texture and delicious taste. However, the growing demand for healthier and functional foods has encouraged the development of ice cream formulations incorporating natural ingredients with health benefits. Purple corn (Zea mays L.) is a rich source of anthocyanins, which act as powerful antioxidants. This study aims to investigate the effect of skim milk and Carboxymethyl Cellulose (CMC) on the physicochemical and organoleptic properties of purple corn extract ice cream. A completely randomized factorial design was used with two factors: skim milk levels (10%, 15%, 20%) and CMC levels (0.1%, 0.2%, 0.3%). The results showed that increasing. Skim milk levels improved overrun, texture, and consumer acceptability, while CMC enhanced viscosity and melting resistance. The combination of 20% skim milk and 0.3% CMC yielded the best overall quality, with high protein content, stable overrun, improved texture, and enhanced antioxidant properties. These findings highlight the potential of purple corn extract as a functional ingredient in ice cream production, offering nutritional benefits and natural anthocyanin pigments. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 2: Good Health and Well-Being SDG 9: Industry, Innovation, and InfrastructureSDG 15: Responsible Consumption and Production